(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The restricted nature reserve „Lielupe flood-plain meadows” was formed to maintain the natural meadows on the banks of the river Lielupe in the territory of Jelgava town. The varied complex of plant communities are located in meadows of Pilssala, on the Lielupe’s right and left bank and thus the nesting of rare and protected meadow and waterbirds as well as important rest area for migrating birds is determined there. The restricted nature reserve is proposed as Natura 2000 place, too. There are the medium moist, moist and wet meadows in the reserve that are the habitats of EU Habitats directive. The biological value of the Lielupe flood plain meadows are currently being endangered by overgrowing and eutrophication. To provide meadows management for maintaining botanical and ornithological values, the inventory of natural meadows was done and proposals for management were developed.